Pengaruh Transparansi, LKPD dan PAD terhadap Kinerja Pemerintah Daerah - Pardomuan Robinson Sihombing*; Ade Marsinta Arsani (LPPM Universitas BSI, 2020)
Local governments' performance reflects the achievement of the goals and objectives set by the agency based on the vision and mission that has been prepared. Many factors affect the performance of local governments, including transparency, accountability of financial statements, and regional income. This study aims to determine the effect of transparency, local government financial report and local own revenue to the performance of local government. The test was conducted in 295 municipalities in Indonesia using secondary data in the form of Local Government Accountability data, Audit Opinions of the BPK and the Budget Realization Report. The results found that both simultaneously and partially Transparency, Regional Government Financial Reports and the Original Revenue of the District had a significant positive effect on the performance of the local government. It means that the increase in transparency, regional government financial reports and local revenue will improve the performance of local government. The implications of this research can be used as a basis for making decisions regarding the management of local revenue, especially in budget transparency, as it can increase public confidence in local governments. The well-prepared financial reports and the management of local revenue for capital expenditure have a direct implication on public services, so that improve local government performance.